‘Iddah Persepektif Al-Qur’an dan Implementasinya dalam Kompilasi Hukum Islam - Widodo, Panggih; Abubakar, Achmad; Dani, Ahmad (Alif Lam : Journal of Islamic Studies and Humanities, 2023)
This research discusses 'iddah in the view of the Qur'an and its implementation in the Compilation of Islamic Law. The purpose of this study is to provide an understanding of 'iddah taken from the verses of the Qur'an and to explore sources of law from the Qur'an regarding the rules of 'iddah in the Compilation of Islamic Law. This is a literature study using primary and secondary data. The results of the study, first, the 'iddah period has the meaning of the waiting period to remarry, especially for post-divorced women, whether divorced lives or dies. Second, there are several discussions about 'iddah in the Qur'an, third, the regulations regarding 'iddah in the Qur'an are implemented in the Compilation of Islamic Law which takes the main source of the 'iddah regulations from the verses of the Qur’an.